పరిణతవాణి (Volume - 3) - (:unkn) unknown (Andhra Saraswata Parishath, 2006)
It's about collection of auto biographical speeches of eminent telugu literary persons
Parinatavani (Volume - 3)
Keywords: Telugu; పరిణతవాణి (Volume - 3); Parinatavani (Volume - 3); Literature; Telugu; Telugu